Utilizing Animated Videos to Improve Listening Abilities in English Language Instruction - KHUMAIRAH, Adelia Rizky; KOROMPOT, Chairil Anwar; SULTAN, Sultan (Research and Innovation in Applied Linguistics, 2023)
This study examined the impact of utilizing animated videos on students' listening skills and their perceptions of this instructional approach. An investigation was conducted using a quasi-experimental pre-test and post-test design, which included a control group. Data was collected by means of listening tests and questionnaires. The participants, comprising 30 students from the ninth grade, were selected using cluster random sampling. Quantitative data analysis was performed using IBM SPSS 20.0. The results indicated a notable distinction in the listening abilities of students in the experimental class when compared to their counterparts in the control class. The two-tailed significance difference yielded a result of 0.006, which is below the alpha level of 0.05. Consequently, The research hypothesis (H1) was corroborated, and the null hypothesis (H0) was invalidated. Additionally, the questionnaire findings demonstrated that students had a favorable perception of integrating animated videos into English language learning, especially in improving their listening abilities. To summarize, utilizing animated videos effectively enhances students' listening skills and is positively regarded as a teaching approach.